Predictors of family burden in parents of children with intellectual disabilities and their children’s sexual development characteristics - Kurt, Aylin; Dinç, Fatma; Güneş Şan, Emine; Uzun, İsmail Berat (European Journal of Clinical and Experimental Medicine, 2025)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Although the existing literature includes both quantitative and qualitative studies that examine the sexual characteristics of children with intellectual disabilities and the challenges they face, these studies have not addressed the impact of these characteristics on the burden of the family. Our objective was to examine the predictors of sexual development of family burden among parents of children with intellectual disability in this cross-sectional study. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. We collected data from 815 parents with children aged 10–18 years with intellectual disabilities between May 2021 and March 2022. Data collection tools were ‘Descriptive Characteristics Form”, “Family Burden Rating Scale for families with Mentally Handicapped Children” and ‘Sexual Development Characteristics scale of Adolescents with Intellectual Disability”. A logistic regression analysis was performed. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The predictive model for the burden of the family explained 60% of the variance in this sample of parents (p<0.001). The sexual predictors with the strongest effect on the model were previous sexual development education (β=0.74; SE=0.16, p≤0.001), followed by sexual harassment (β=-0.56, SE=0.26, p≤0.001). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Education on sexual development in children with intellectual disability can facilitate management of challenges in adolescence.